The Role of Teachers in Facilitating The Development of Emotional Intelligence of Students: A Case Study of SMK Students in Surakarta - Kusumawati, Nuur Roofiah; Budiyanto, Cucuk Wawan; Siyamtiningtyas, Yuliyani (Universitas Sebelas Maret, 2023)
The development of the world of education in Indonesia has adapted to the global dynamics and demands of the evolving world of work. Emotional intelligence, which includes self-awareness, emotional control, self-motivation, empathy, and collaborative skills, is recognized as the key to preparing younger generations for the complexities of the globalization era. This research focuses on the High School of Teaching (SMK) in Surakarta, Indonesia, where emotional intelligence becomes a crucial aspect, in addition to technical expertise. Daniel Goleman suggests that individual success is more influenced by emotional intelligence than intellectual intelligence. This research uses qualitative research methods with a descriptive approach with data collection performed by observation and interview. Participants were selected purposely for sampling because they had a deep understanding or experience of the subject being studied, namely students of the XI RPL class. The results of the study on the development of emotional intelligence of SMK students showed the role of teachers in helping students develop self-awareness and manage emotions effectively. Students showed improvements in the aspects of self-awareness, emotional control, self-motivation, empathy, and collaboration during learning. The teacher's role as a facilitator and mentor became crucial in creating a positive learning environment. Teachers not only provide lessons but also guide students in facing challenges and conflicts wisely.